Microstructural evolution and strengthening mechanism of U71Mn steel joints fabricated by friction-flash hybrid welding - Jiaqing You; Jinhong Tan; Xingping Liu; Kai Du; Jiarui Li; Chengyang Yi; Yunqiang Zhao (Materials & Design)
The softening layer formed by the ferrite in the welding interface can significantly reduce the mechanical properties of traditional flash butt welding joints. This study proposed a flash-friction hybrid welding method to address the issue of the ferrite softening layer and comprehensively investigated the impact of vibration friction speed on joint performance. The results showed that increasing the vibration friction speed could effectively inhibit the formation of the ferrite softening layer in the weld center zone (WCZ) and enhance the mechanical properties of the joint. When the vibration friction speed was 3 mm/s, the tensile strength of the joint reached its maximum value of 982.9 MPa, approximately equal to 97.3 % of that of the base material (BM). The fracture occurred in the heat-affected zone (HAZ) and was characterized by a ductile fracture mechanism. Moreover, the microstructural analysis revealed that dynamic recrystallization (DRX) occurred in the WCZ, thermo-mechanically affected zone (TMAZ), and fine-grained zone (FGZ)-HAZ of the joint. Compared to the BM, the grain size significantly decreased, and the thickness and spacing of lamellar cementite also reduced. These microstructural evolutions also contributed to the enhanced mechanical properties of the joints. This study provided new insights for welding in the rail transportation field.